Conversations in Indian history - U.P. History Congress 2008 : Department of Medieval and Modern Indian History, University of Allahabad); Sinha, A. K.; Jafri, Saiyid Zaheer Husain (New Delhi : Anamika Publishers & Distributors, 2010)
Contributed articles presented at the 19th Session of the U.P. History Congress organized under the aegis of the Dept. of Medieval and Modern Indian History, University of Allahabad on Oct. 18-19, 2008.
English and Hindi.
Keywords: India -- History -- Congresses